Intra-articular landmarks for anterior cruciate ligament reconstructions: a review. (December 2010) - Bicer, Elcil Kaya; Magnussen, Robert A; Jacobi, Matthias; Lustig, Sebastien; Servien, Elvire; Neyret, Philippe
Although many factors influence outcome following anterior cruciate ligament reconstruction, recurrent instability is frequently linked to technical errors, most commonly tunnel malposition. Numerous anatomic landmarks have been described in order to aid in accurate tunnel placement. This article will review and summarize the current literature regarding intra-articular landmarks and their use in anterior cruciate ligament reconstruction.